Frequency stability analysis of power grid during photovoltaic generation in Hail region (Arabia Saudi) - Kahouli, Omar (Frontiers in Energy Research, 2025)
Increases in power generated by renewable energy sources (RES) that suffer from low-moment inertia could be hazardous to the power system's capability to operate reliably and consistently. Because RESs do not have rotating parts, their penetration into modern power systems may result in a reduction in the system's inertia, which is directly related to the power grid stability issue. This reduction in rotational inertia associated with synchronous generation may increase the rate of frequency changes, reducing frequency control performance. It is important to investigate frequency stability under disturbances in such systems. The main objective of this research is to evaluate the technical viability of supplying an inertial response in power grids with high photovoltaic (PV) power penetration utilizing energy storage devices based on batteries. The case study of this work includes a 147.9 kW PV system connected to the national power grid of Hail City, which is located in the north of Riyadh, the capital of Saudi Arabia. In this paper, batteries are recommended to improve the stability of the frequency. The inertia of the proposed system varied via adjusting the penetration degree of RES. This evaluation was carried out using the voltage source inverter model under droop control. A detailed model provincial power network is built using MATLAB/Simulink to assess the effects of large-scale penetration of RES on frequency stability. Two important points that will distinguish our study from the other studies that use droop control inverters and battery systems are the same model.